The role of T cell immunity in natural influenza A infection in a UK cohort: flu watch - Wang, L (2014)
A novel influenza A virus bearing the characteristics of high virulence, the ability to infect humans and transmit from human to human, such as the pandemic influenza of 1918, could lead to millions of deaths. The 2009 influenza pandemic demonstrated that a novel influenza A virus could spread globally in a few months despite the availability of modern comprehensive surveillance systems and systemic prevention and control measurements. Novel pandemic strains that could occur naturally or be created in laboratory, pose a serious threat to public health. Current available vaccines are capable to induce neutralizing antibodies against the viral surface antigen hemagglutinin (HA), which provide sterilizing immunity by blocking infection. However this antibody protection is serotype specific and therefore offers limited or no protection against a serologically distinct influenza virus. An alternative vaccine approach is the induction of cross-protective T cell immunity, directed at influenza A conserved internal proteins which could potentially offer broad protection against different influenza strains in humans. This approach may complement antibody-inducing vaccines and greatly enhance the protective efficacy of influenza vaccines. This study builds on previous evidence derived from animal models and human experimental challenge studies, to demonstrate the heterotypic T cell immunity in the context of natural influenza A infection in humans. Pre-existing influenza A specific T cell immunity was quantified by human IFN-γ ELISpot assay and was detectable in over 70% of Flu Watch participants. Nucleoprotein was the most immunodominant viral protein; and the most potent viral protein in eliciting influenza A specific CD8+ T cells. The nucleoprotein specific T cells exhibited high level of cross reactivity to the 2009 pandemic influenza and reduced the occurrence of nasal viral shedding in the absence of antibody immunity, following acquisition of pandemic influenza infections. This study provides evidence to support the development of a T cell based influenza vaccine, and provides important evidence to empower future studies of this kind.